2016
DOI: 10.1016/j.bbagen.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol preferentially inhibits IgE-dependent PGD2 biosynthesis but enhances TNF production from human skin mast cells

Abstract: Background Resveratrol, a natural polyphenol found in the skin of red grapes, is reported to have anti-inflammatory properties including protective effects against aging. Consequently, Resveratrol is a common nutritional supplement and additive in non-prescription lotions and creams marketed as anti-aging products. Studies in mice and with mouse bone marrow-derived mast cells (BMMCs) have indicated anti-allergic effects of Resveratrol. However, the effects of Resveratrol on human primary mast cells have not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 51 publications
3
21
0
Order By: Relevance
“…Although several studies suggest the protective effect of resveratrol against allergic responses 2227 , the precise role of Sirt1 in FcεRI-mediated mast cell activation has not been firmly established. In this study, we have shown that resveratrol blunts FcεRI signaling partly through the activation of Sirt1, which is linked to the LKB1/AMPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies suggest the protective effect of resveratrol against allergic responses 2227 , the precise role of Sirt1 in FcεRI-mediated mast cell activation has not been firmly established. In this study, we have shown that resveratrol blunts FcεRI signaling partly through the activation of Sirt1, which is linked to the LKB1/AMPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol was confirmed to protect skin against photo damage through enhancing skin moisture and elasticity, reducing depth and length of wrinkles and decreasing intensity of spots [49][50][51]. In vitro test revealed that resveratrol directly inhibited degranulation of RBL-2H3 mast cells and human skin mast cells [52,53]. Resveratrol was reported to decrease the phosphorylation of ERK 1/2 in activated human mast cell-1(HMC-1) cells and inhibit NF-κB activation, which in turn lead to suppressed expression of TNF-α, IL-6, IL-8 and cyclooxygenase (COX)-2 [54].…”
Section: Resveratrolmentioning
confidence: 96%
“…Notably, the presence of both IL-1α and TNF-α is a strong indication of inflammation. Moreover, TNF-α in the skin is produced mainly by activation of resident dermal mast cells [ 29 ]. Those cells contain numerous sizable active TNF-α inside their granules, which can be rapidly released to the extracellular space upon degradation of the cells.…”
Section: Discussionmentioning
confidence: 99%